On the food and feeding habit of an estuarine catfish (Mystus gulio Hamilton) in the south-west coast of Bangladesh - Begum, M; Alam, MJ; Islam, MA; Pal, HK (University Journal of Zoology, Rajshahi University, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> No Abstract doi:10.3329/ujzru.v27i0.1962 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 91-94